Outcome of diffuse large B-cell lymphoma patients treated with different chemotherapeutic regimens (R-DA-EPOCH vs R-CHOP) (BIRDEM Medical Journal, 2022)
Background: Diffuse large B-cell lymphoma (DLBCL) is a heterogeneous group of hematological malignancy of large B lymphocytes with a diffuse growth pattern. It is the most common type of adult non-Hodgkin lymphoma (NHL), making up to 30-40% of NHL. Although DLBCL is potentially curable, it remains a challenging lymphoma to manage because of the biological and clinical heterogeneity of the disease.Aim of the study was to compare the outcome of different chemotherapeutic regimens in newly diagnosed DLBCL patients.Methods: This quasi-experimental study was conducted at Department ofHematology,Dhaka Medical College Hospital(DMCH) from January 2018 to June 2019 including nineteen newly diagnosed DLBCL with stage I to IV A/B cases. Protocol was approved by ethical review committee (ERC) of DMCH. Patients aged e”18 years and < 65 years were enrolled for this study and were divided into two groups as arm A treated with rituximab plus cyclophosphamide, doxorubicin, vincristine, prednisone (R-CHOP) (10 cases) and arm B treated with rituximab plus dose adjusted etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin (R-DA-EPOCH)(9 cases).Results: Mean age of all patients was 41 years (range 16 to 60 years). Majority (69%) of the patients were below 50 years of age and M: F ratio was 2:1.Seventy percent of patients had Ann Arbor stage III or IV disease in R-CHOP arm and 67% in R-DA-EPOCH arm although international prognostic index (IPI) score was variable (0-4). Raised serum lactate dehydrogenase (LDH) was observed in 70% and 89% of R-CHOP and R-DA-EPOCH arms respectively. Almost 50% of patients were germinal-center B-cell-like (GCB) diffuse large B-cell lymphoma (DLBCL) in each arm.In arm A, out of ten patients, five (50%) achieved complete remission (CR), one (10%) achieved partial response(PR), three (30%) had progressive disease (PD) and overall response (OR) rate was 60%. In arm B, out of nine patients, five (56%) achieved CR, two (22%) had progressive disease (PD) and two (22%) patients died. In subgroup analysis of outcome of GCB group, there was equal CR rate in both arms(60%, p=0.57), whereas in non-GCB arm, CR was found 40% vs. 50% in R-CHOP vs. R-DA-EPOCH arm respectively (p=0.89).Conclusion: From the result of this study it can be concluded that, there was no statistically significant difference in respect of outcome of chemotherapy among patients treated with R-DA-EPOCH and R-CHOP.BIRDEM Med J 2022; 12(3): 188-194